First occurrence of Lingulepis (Brachiopoda-Obolidae) from the Devonian of the Paraná state, Brazil - Bosetti, Elvio Pinto; Horodyski, Rodrigo Scalise; Zabini, Carolina; Matsumura, Willian Mikio Kurita; Godoy, Luiz Carlos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
The brachiopod fauna of the Paraná State Devonian sucession (Neo-Lochkovian – Frasnian) is known for a long time. In the present paper a new species of Brachiopoda, Lingulepis wagoneri sp. nov. (Linguliformea – Lingulata – Obolidae) is recorded and described for the Paraná Basin Devonian. It is the first occurrence of this genus in Brazil. All specimens were preserved in siltstone shale and dark-gray siltstone and were collected in Ponta Grossa and Tibagi outcrops, located in the eastern portion of the Paraná Basin.
Keywords: Lingulepis wagoneri; Devonian; Paraná Basin